(untitled) (Heritage, 2020)
In the study of the consequences of intense trauma, we find numerous consequences for people who survived it and who live in postwar environment. A number of authors report strong and sustained reactions of persons who have experienced a traumatic event, especially the expression of depressive, anxiety and somatic symptoms in persons exposed to war stress, for example in persecution, fighting, trapping etc. Interest in the psychological effects of war has skyrocketed over the last twenty five years. The two leading approaches to understanding the mental health of people affected by war are the trauma-focused approach and the psychosocial approach. This paper deals with war traumatic experiences of the population from Kosovo and Metohija and their impact on mental health. Direct influence exists, based on a trauma-focused approach, where a critical factor is direct exposure to violence and the devastating effects of war, the most important factor affecting mental health. Following the existing models on the basis of theoretical foundations as well as the psychosocial approach which considers the role of stressful social and material conditions that emerge in the post-war years in Kosovo and Metohija on mental health, the authors come up with the idea to examine the mediating impact of these conditions. Revising the current model authors postulated a model of war traumatic experiences and their effects on mental health mediated by social and material conditions. Structural equation modeling was used to test the fit of the model. The assumption of the mediating role of stressful social and material conditions caused by war traumatic experiences on adult mental health was confirmed. The tested model, with the proposed modifications, showed agreement with the empirical data.